Polyarticular heterotopic ossification complicating drug induced coma - S. Antonelli; G.D. Sebastiani (PAGEPress Publications, 2002)
The Authors describe a case of generalised heterotopic ossification (HO) complicating the course of a 31 years old male patient, with a history of Hodgkin's lymphoma and a of long staying in an intensive care unit, where he had been placed on artificial coma. The clinical features, as well as radiological findings and therapy, are discussed.